(untitled) (International journal of artificial intelligence, 2025)
The article analyzes the life and historical activity of Joan of Arc, the national heroine of the French people who lived in the first half of the 15th century. The paper examines the events of her struggle for the liberation of the French nation from foreign invaders, her influence on the course of the war, as well as her trial and death. The article reveals Joan of Arc’s place in European history and her significance as a symbol of female courage.